IMPLEMENTASI ELECTRONIC COMMERCE SEBAGI MEDIA MARKETING PRODUK HOME INDUSTRI DI KERAJINAN TAPIS PADANG CERMIN PESAWARAN - Megasari Megasari (Jurnal Signaling, 2023)
Information technology is developing very rapidly and the positive impact we can feel is helping and making work easier. The development of information technology in this modern era can encourage people to use technology in various fields, one of which is in the business sector. Information technology has been a major catalyst in changing the way of doing business. With the existence of information technology, it will make it easier to do business. In designing this sales application, it is carried out by implementing Mobile Commerce which is intended to assist sellers in promoting products or introducing products to increase product sales. This research aims to help or facilitate the Home Industry of Tapis Padang Cermin Craft to carry out promotions and buying and selling transactions as an effort to increase sales. Methods in solving this problem using observation data collection techniques, interviews, and literature study. Meanwhile, in an effort to develop sales and marketing information systems using the Waterfall method. The results of this study are designing E-Commerce for home industry products Tapis Padang Cermin Pesawaran Lampung which aims to increase marketing and sales.